Sexual dysfunction, body image distress and marital dissatisfaction in breast cancer patients of University Malaya Medical Centre (UMMC) / Norley Shuib - Norley, Shuib (2014)
Sexual dysfunction, body image distress and marital dissatisfaction in breast cancer patients of University Malaya Medical Centre (UMMC) Introduction: Breast cancer is the commonest cancer amongst Malaysian women. Recent literature has shown that, the disease itself and adverse effects of the cancer treatment were associated with sexual dysfunction, body image distress and marital dissatisfaction. Aim: The aim of the study is to determine the prevalence of sexual dysfunction in breast cancer patients who are in remission attending follow-up at the breast clinic in UMMC. Method: This is a cross-sectional study conducted at the breast clinic in UMMC. The patients were given self-reported questionnaires, the Female Sexual Function Index (FSFI), Breast Impact of Treatment Scale (BITS), Golombok Rust Inventory of Marital State (GRIMS), Hospital Anxiety and Depression Scale (HADS) and Psychological General Well-Being Index (PGWBI). Socio-demographic, clinical, disease and marital data were obtained by interviewing the patients and also reviewing the medical notes. Ethical approval for the study was obtained from the Ethics Committee of UMMC. iii Results: A total of 100 breast cancer patients were recruited. The prevalence of sexual dysfunction as assessed by the Female Sexual Function Index (FSFI) with the cut-off score of ≤ 26.6 was 90.0%. By using the Breast Impact of Treatment Scale (BITS), the prevalence of body image distress was 42.9%. The prevalence of marital dissatisfaction determined by the Golombok Rust Inventory of Marital State (GRIMS) was 55.0%. The Hospital Anxiety and Depression Scale (HADS) was used to assess depression (prevalence of 9.0%) and anxiety (prevalence of 27.0%). Actual age of disease onset, total GRIMS score (marital dissatisfaction) and HADS-D sub-scale score (depression) were found to be independently associated with sexual dysfunction. Conclusion: Breast cancer survivors experienced great level of sexual dysfunction, body image distress, marital dissatisfaction, depression and anxiety. These findings serve as an alarm for health care providers for early and routine assessment of these matters. A prompt referral to the mental health services may be required for further evaluation and appropriate treatment when indicated.